Role of MicroRNA in Chronic Alcoholic and Non-alcoholic Liver Disease and Pathology - Patra, Biswanath; Arya, Vikram (International Journal of Bio-resource and Stress Management, 2014)
MicroRNAs (miRNA) are highly conserve non-coding RNAs which regulate gene expression, different aspect of cell signaling, cellular activity, cell differentiation and development, metabolism, proliferation, programmed cell death, viral and bacterial infection and oncogenesis etc. Current findings suggest that miRNAs are plentiful in liver and regulate large number of liver function. Perturbation of miRNA expression is a key genetic factor in many liver diseases including Alcoholic Liver Disease (ALD), Alcoholic Steatohepatitis (ASH), Non-alcoholic Steatohepatitis (NASH), viral hepatitis, hepatocellular cancer and polycystic liver diseases. The mechanisms involved in miRNA deregulation will offer new diagnostic and therapeutic strategies for the treatment of liver diseases. In addition, better understanding of miRNA regulation and identification of tissue-specific miRNA expression will improve our knowledge of liver physiology and diseases.